Formation of an Airway Lead Network: an essential patient safety initiative. (February 2022) - Baker, Paul A.; Behringer, Elizabeth C.; Feinleib, Jessica; Foley, Lorraine J.; Mosier, Jarrod; Roth, Patricia; Wali, Ashutosh; O'Sullivan, Ellen P.
Summary: We outline the history, implementation and clinical impact of the formation of an Airway Lead Network. Although recommendations to improve patient safety in airway management are published and revised regularly, uniform implementation of such guidelines are applied sporadically throughout the hospital and prehospital settings. The primary roles of an Airway Lead are to ensure supply, quality and storage of airway equipment, promote the use of current practice guidelines as well as the organisation of training and audits. Locally, the Airway Lead may chair a multi-disciplinary airway committee within their organisation; an Airway Lead Network enables Airway Leads to share common problems and solutions to promote optimal airway management on a national level. Support from governing bodies is an essential part of this structure.